2009
DOI: 10.1007/s10585-009-9274-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of survivin-expressing circulating cancer cells in the peripheral blood of patients with esophageal squamous cell carcinoma and its clinical significance

Abstract: We previously demonstrated that the detection of circulating cancer cells (CCC) expressing survivin mRNA could provide valuable information for predicting recurrence in patients with breast, lung, gastric and colorectal carcinoma. The purpose of this study is to investigate whether the detection of survivin-expressing CCC in the peripheral blood is also useful for predicting recurrence in patients with esophageal squamous cell carcinoma (ESCC). Blood samples obtained from 108 ESCC patients and 75 healthy volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…There left 32 full-text articles for detailed evaluation, of which 19 studies were further excluded for being incompatible with inclusion criteria [11–15], without survival data to estimate HRs and 95% CIs [1, 16–24, 32] or with less than 20 samples [2527] (Supplementary Table 1). Finally, 13 eligible studies were included for meta-analysis [9, 10, 28–31, 33–39]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There left 32 full-text articles for detailed evaluation, of which 19 studies were further excluded for being incompatible with inclusion criteria [11–15], without survival data to estimate HRs and 95% CIs [1, 16–24, 32] or with less than 20 samples [2527] (Supplementary Table 1). Finally, 13 eligible studies were included for meta-analysis [9, 10, 28–31, 33–39]. …”
Section: Resultsmentioning
confidence: 99%
“…In recent years, studies of peripheral blood CTCs suggest that CTCs can be used to predict the progress and prognosis of esophageal cancer [9, 10]. However, current research findings on esophageal CTCs are based on small cohorts of tumor specimen and results are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of CTCs expressing survivin (an apoptosis inhibitor) by an RT-PCR enzyme-linked immunosorbent assay, developed by Yei and colleagues, provided important predictive information for breast cancer metastasis and recurrence [156]. The same team then used this technique to demonstrate that survivin expression in CTCs from patients with gastric cancer, CRC and esophageal squamous cell carcinoma was associated with disease stage, decreased survival and a higher relapse risk [157,158].…”
Section: Gastrointestinal Cancersmentioning
confidence: 99%
“…Due to its high expression in most human cancers, and its ability to play a key role in promoting cell proliferation, it is considered to be a potentially important therapeutic target [10]. Moreover, several studies have shown the diagnostic value of survivin-expressing CTCs in patients with cancer [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%